2019
DOI: 10.20885/ajim.vol1.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Customers attitude toward Islamic mobile banking in Indonesia: Implementation of TAM

Abstract: This study aims to test consumer acceptance of mobile banking Islamic banks using the Technology Acceptance Model. The concept of mobile banking is used to examine the role of banking in facilitating mobile consumer financial transactions. Methodology: This study uses a survey with a sample of 179 users of mobile banking applications Islamic banks in Central Java and Yogyakarta. Data analysis used in this study is SEM with AMOS software assistance Findings: All hypotheses are supported. Based on the consumer's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 13 publications
3
17
0
5
Order By: Relevance
“…Several findings have focused on electronic service quality on banking customer loyalty (Amin, 2016;Cahaya & Siswanti, 2020). However, these findings only focus on internet banking and the antecedent factors of customer attitudes towards mobile banking adoption behavior (Raza et al, 2020;Shaikh & Karjaluoto, 2015;Riza & Hafizi, 2019). Therefore, it is crucial to carry out an in-depth investigation of m-banking from a relationship marketing perspective (Arcand et al, 2017;Tumewah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several findings have focused on electronic service quality on banking customer loyalty (Amin, 2016;Cahaya & Siswanti, 2020). However, these findings only focus on internet banking and the antecedent factors of customer attitudes towards mobile banking adoption behavior (Raza et al, 2020;Shaikh & Karjaluoto, 2015;Riza & Hafizi, 2019). Therefore, it is crucial to carry out an in-depth investigation of m-banking from a relationship marketing perspective (Arcand et al, 2017;Tumewah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Digital Banking is a new term in banking industry in Indonesia (Riza & Hafizi, 2019). Digital banking implements all banking services and operations in digital devices (Nguyen et al, 2018).…”
Section: Literature Review Digital Bankingmentioning
confidence: 99%
“…Bank operational risk management must be carried out properly to improve service performance and superior innovation in an unstable environment (Sembiring, 2020;Disemadi & Shaleh, 2020). It is shown that the use of banking technology has a positive impact (Nam et al, 2016;Riza & Hafizi, 2019;Wijayanti & Riza, 2017). Since the launching of the Branchless Banking system in 2013, it has been proven that digital banking services have succeeded in reaching the unbanked and underbanked people (Bank Indonesia, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Reliability and validity testing is required before testing structural models (Cooper & Schindler, 2011a) & (Riza & Hafizi, 2019). The validity test is carried out by looking at the estimated value / loading factor, the item is said to be valid if the value is> 0.50 and the reliability test is assessed using Cronbach Alpha, the variable construct is said to be reliable if the value is> 0.60.…”
Section: Validity and Reliability Testmentioning
confidence: 99%